Improving Milk Quality and Udder Health of Etawah Crossedbred Goat by Good Milking Procedure - Suranindyah, Yuni (2013)
The purpose of this study was to compare the effect of milking procedure on milk quality and udder health of Etawah Crossed bred goats. The study was conducted in the farmer group in the village of Samigaluh Kulon Progo. Twelve lactating goats were devided into Control and Treated groups. Milking goats of the Control group in the milking stand followed with teat diping. Sample was taken after milking in the morning. Examination was conducted to evaluated the milk taste and smell and to measure acidity, pH, total plate count (TPC) and somatic cell count (SCC). The result showed that pH and acidity of milk in the control group was significantly lower than that in the Treated group (P<0.05). Treatment could reduce milk taste (sour and bitter) and odor (smell prengus) but no effect on TPC and SCC. Teat dipping reduced SCC. The study concluded that good milking practiced by using milking stand combined with teat dipping improved milk quality and udder health of goats. Key words: Milking, Goat, Milk quality, Udder health